Lactogenic hormone stimulation and epigenetic control of L‐amino acid oxidase expression in lactating mammary glands. Issue 11 (November 2015) - Fujii, Kazuki; Zhang, Haolin; Usuda, Kento; Watanabe, Gen; Nagaoka, Kentaro
<x xml:space="preserve">Abstract</x> L‐amino acid oxidase (LAO), a classic flavoprotein, shows antibacterial activity by producing hydrogen peroxide. LAO exists in many tissues such as salivary gland, thymus, spleen, small intestine and testis. In particular, LAO was highly expressed in mice milk and plays an important factor in innate immunity of mammary glands. However, the mechanism which LAO expression is regulated spatially and temporally in lactating mammary glands has been unclear. In this study, we showed the contribution of lactogenic hormone and epigenetic control on LAO gene expression. In monolayer of mammary epithelial cells, treatment of lactogenic hormone mixture, dexamethasone, insulin and prolactin, did not induce LAO mRNA expression and its promoter activity, even though one of milk protein β‐casein expression was stimulated. However, increase of LAO expression was observed when the cells were treated with lactogenic hormones in a 3‐dimensional culture. The results of chromatin immunoprecipitation analysis revealed that histone H3K18 acetylation increased and histone H3K27 tri‐methylation decreased with lactation, which is associated with a period of high LAO expression. Moreover, the treatment of histone methylation inhibitor (DZNep) as well as histone deacetylation inhibitor (Trichostatine A) induced LAO expression in monolayer of mammary cells. Taken together, this is the first demonstration showing that LAO expression is induced in cell culture, and stimulation of lactogenic hormone and change of histone modification are promising signals to show highly expression of LAO in lactating mammary glands. J. Cell. Physiol. 9999: 2755–2762, 2015. © 2015 Wiley Periodicals, Inc.